Stein manifolds and holomorphic mappings the homotopy principle in complex analysis - Forstnerič, Franc 1958- (Springer, 2017)
The theme of this book is an examination of the homotopy principle for holomorphic mappings from Stein manifolds to the newly introduced class of Oka manifolds, offering the first complete account of Oka-Grauert theory and its modern extensions
Keywords: Stein manifolds; Holomorphe Abbildung; Stein-Mannigfaltigkeit